Apparent Life Threatening Event and gastric antral ulcer in a full-term infant: any possible relationship? - Bacchini, P.L.; Romanini, E.; Magnani et al., C. (Acta Biomedica Atenei Parmensis, 2010)
We describe the case of an apparently healthy newborn infant who in 7th day of life showed an episode of haematemesis and in 13th day of life presented an episode of apparent life threatening event (ALTE). A fibroscopy of the upper digestive tract showed a great ulcer of the gastric antrum and  esophagitis limited to the mucosa. Gastrinemia in the blood showed high values (121 pg/ml). The relationship between ALTE and gastric ulcer may be casual, however in literature a gastroenteric cause is present in about 50% of ALTE in which an etiologic cause is found. We speculate that in the present case the increase of gastrin secretion reduced gastric pH which facilitated the onset of gastric ulcer and esophagitis with ALTE due to pain or reflex.